Quantification of ferry traffic in the Canary Islands (Spain) and its implications for collisions with cetaceans - Ritter , Fabian (J. Cetacean Res. Manage., 2023)
The Canary Islands, known for their high cetacean species diversity, have witnessed a rapid expansion of fast ferry traffic during the past few years. At the same time, ship strikes have been repeatedly documented. In this paper an overview of the inter-island ferry traffic in the archipelago is given. Ferry types in use (normal, fast and high speed vessels) are described, and the transects on which they operate are identified. To quantify the extent of the inter-island ferry traffic, three parameters were determined: (1) the actual transects from the different ports on the islands; (2) the number of journeys made per week on each transect; and (3) the length of each transect. Resulting numbers indicate that normal ferries travel approx. 66,000km, fast ferries travel approx. 570,000km and high speed ferries travel approx. 845,000km between islands each year. Fast and high speed ferry traffic is concentrated in the western islands. Areas of high risk for ship strikes within the archipelago are identified by comparing the location of transects with known areas of high cetacean abundance. It is argued that the Canary Islands are a hot spot for vessel-whale collisions and that a policy to counteract this situation is urgently needed.